Dakar Wolof A Basic Course - Nussbaum, Loren V.; Center for Applied Linguistics, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This basic course in Dakar Wolof, based on the "Introductory Course in Dakar Wolof" by William A. Stewart, et al. (1966), is designed to be taught audiolingually by a native speaker of the language. It is suggested that the class meet three or more hours per day with size limited to six to 10 students. Dakar Wolof, which is not a "written" language, is the dialect of Wolof currently used in Dakar, Senegal and is the predominant language of two ethnic groups, the Wolofs and the Lebus. The text is comprised of 74 lessons. The even-numbered lessons focus on social interaction (e.g. greetings, classroom phrases, language learning tools, and explorations of the immediate environment), while the odd-numbered lessons concentrate on the development of grammatical understanding of the language. Textual materials conclude with a vocabulary list of words in Wolof with English equivalents. (RL)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEC-0-9-097707-4406-014.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: African Languages; Audiolingual Methods; Basic Skills; Curriculum Guides; Grammar; Instructional Materials; Language Instruction; Language Learning Levels; Lesson Plans; Modern Languages; Teaching Guides; Textbooks; Wolof; Senegal -- Senegal (Dakar)